Women and Men Teachers in Italy from the Fall of the Old Regime to the Rise of Fascism. Birth and development of a profession - de Fort, Ester (Historia y Memoria de la Educación, 2015)
The article examines the slow process of professionalization of elementary school teachers, from the fragmented educational reality of the old regime to the emergence of a teaching body with a specific preparation and a collective identity. The Italian State played a significant role in this process because it concerned itself with the requalification of teachers and the education of new students up to the demanding task of fighting the high levels of illiteracy and promoting people’s adherence to the new values on which it was based. Teaching, however, remained poorly paid and quite precarious and those aspects increased feminine recruitment: the job was considered a respectable and typically womanly occupation, even though the arrival of single girls in small provincial towns sometimes resulted into persecutions that found an echo in press and literature. The improvement of teachers’ cultural level made untenable the contradiction between the rhetoric exaltation of the role of the teacher and the real conditions of the profession, which also contributed to the pedagogical press. In the new century, an increasingly combative association movement developed which obtained important results, but was undermined by deep internal divisions, between men and women, urban and rural teachers, catholic and secular teachers. Teachers were accused of defending corporative interests and neglecting the school system needs, and then called to order by the Gentile’s education reform, one of the first acts of Fascist rule.